2017
DOI: 10.3390/life7020016
|View full text |Cite
|
Sign up to set email alerts
|

Self-Referential Encoding on Modules of Anticodon Pairs—Roots of the Biological Flow System

Abstract: The proposal that the genetic code was formed on the basis of (proto)tRNA Dimer-Directed Protein Synthesis is reviewed and updated. The tRNAs paired through the anticodon loops are an indication on the process. Dimers are considered mimics of the ribosomes—structures that hold tRNAs together and facilitate the transferase reaction, and of the translation process—anticodons are at the same time codons for each other. The primitive protein synthesis system gets stabilized when the product peptides are stable and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 131 publications
(183 reference statements)
1
2
0
Order By: Relevance
“…In addition, mean CDA decreases with the order of inclusion of amino acids in the genetic code, according to the majorities of genetic code inclusion hypotheses as reviewed in [14], in agreement with genetic code evolutionary hypotheses that assume that class II tRNA synthetases and their cognate amino acids were first included in the genetic code [15,16]. This negative correlation is strongest (r = −0.775) with the genetic code inclusion order derived from the genetic code origin self-referential model [17] (presumed earliest to presumed latest amino acids: G, S, L, D, N, E, P, K, F, R, A, C, T, V, H, Q, I, M, Y and W).…”
Section: Cda and Properties Of The Translational Apparatus The Genetsupporting
confidence: 73%
“…In addition, mean CDA decreases with the order of inclusion of amino acids in the genetic code, according to the majorities of genetic code inclusion hypotheses as reviewed in [14], in agreement with genetic code evolutionary hypotheses that assume that class II tRNA synthetases and their cognate amino acids were first included in the genetic code [15,16]. This negative correlation is strongest (r = −0.775) with the genetic code inclusion order derived from the genetic code origin self-referential model [17] (presumed earliest to presumed latest amino acids: G, S, L, D, N, E, P, K, F, R, A, C, T, V, H, Q, I, M, Y and W).…”
Section: Cda and Properties Of The Translational Apparatus The Genetsupporting
confidence: 73%
“…Arg is also coded by GC-rich codons, but the authors omitted it from the earliest encoded amino acids since most (but not all) simulation experiments suggested that Arg was not present under prebiotic conditions [8]. The coevolution hypothesis of the genetic code proposed that the encoding of new amino acids was determined by the evolution of their synthetic pathways within the primordial biochemical system [1,9,10]. While this hypothesis may be valid for certain late amino acids, it is unlikely to be correct for the earliest of them, as this would demand complex protein-based enzymatic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, primordial tRNA-like molecules (not real tRNAs) of the same origin may have evolved (Figure 6). Based on the knowledge of the tRNA-rRNA homologies [48], tRNA dimers may also have been mimics of the ribosome [49]. On the other hand, faced with the metabolic paradoxes of purine and pyrimidine biosynthesis, i.e., purine and pyrimidine rings are synthesized from glycine and aspartic acid, respectively [50], one possibility may be peptide nucleic acids (PNA) as a precursor to RNA [51].…”
Section: Discussionmentioning
confidence: 99%